2017
DOI: 10.3892/etm.2017.5004
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane exposure in postnatal rats induced long-term cognitive impairment through upregulating caspase-3/cleaved-poly (ADP-ribose) polymerase pathway

Abstract: Abstract. The association of anesthetic exposure in infants or young children with the long-term impairment of neurologic functions has been reported previously; however, the underlying mechanisms remain largely unknown. In order to identify dysregulated gene expression underlying long-term cognitive impairment caused by sevoflurane exposure at the postnatal stage, the present study initially performed behavioral tests on adult Wistar rats, which received 3% sevoflurane at postnatal day 7 (P7) for different ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Although we have not performed a direct measurement of apoptosis, increased cleaved PARP levels have been considered a marker of apoptosis because this protein is the substrate of activated caspases 43 . In agreement, upregulation of Caspase 3 gene expression in a model of cognitive impairment induced by sevoflurane was associated with increased cleaved PARP levels 44 . While Caspase 3 is an effector caspase, being part of the final common pathway of apoptosis, Cytochrome c, APAF 1, and Caspase 9 integrate the intrinsic apoptotic pathway.…”
Section: Discussionsupporting
confidence: 64%
“…Although we have not performed a direct measurement of apoptosis, increased cleaved PARP levels have been considered a marker of apoptosis because this protein is the substrate of activated caspases 43 . In agreement, upregulation of Caspase 3 gene expression in a model of cognitive impairment induced by sevoflurane was associated with increased cleaved PARP levels 44 . While Caspase 3 is an effector caspase, being part of the final common pathway of apoptosis, Cytochrome c, APAF 1, and Caspase 9 integrate the intrinsic apoptotic pathway.…”
Section: Discussionsupporting
confidence: 64%
“…It is shown that COX-2 was inhibited by caspase-3 after irradiation, and the inhibition of COX-2 could sensitize cancer cells to apoptosis [22,23]. RAPR is another important substrate of caspase-3, in which it is decomposed to an 85-kDa product, cRAPR, that can be identified as an apoptotic marker [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…3% seveflurane was used to construct the injury model, the concentration of which was just higher than that commonly used in clinical application and was commonly used in researches too (6,26), The groups were named LBP100+SEV, LBP200+SEV, LBP400+SEV, LBP600+SEV groups, respectively, Cells treated with 3% sevoflurane gas alone were named SEV group, Cells treated with 400 ”g/ml LBPs were named LBP400 group, and cells without any treatment were considered as Control group.…”
Section: Methodsmentioning
confidence: 99%